Working in travel and tourism - McAlpine, Margaret (Milwaukee, Wis. : Gareth Stevens Pub., 2005)
Introduces preteens to seven careers in the field of travel and tourism, including flight attendant, tour guide, and travel agent, each with a description, outlines of basic responsibilities and qualifications, and a look at a typical day on the job.
Includes bibliographical references (p. 62) and index.
Horn Book, April 2005.
Horn Book.
7.8
5-8
Keywords: Tourism -- Vocational guidance -- Juvenile literature; Tourism -- Vocational guidance; Tourism -- Vocational guidance; Tourist trade -- Vocational guidance